2016
DOI: 10.1530/erc-16-0013
|View full text |Cite
|
Sign up to set email alerts
|

NG2 targets tumorigenic Rb inactivation in Pit1-lineage pituitary cells

Abstract: The proteoglycan neuron-glial antigen 2 (NG2) is expressed by oligodendrocyte progenitors, pericytes, and some cancerous cells where it is implicated in tumor development. We examined mice with NG2-driven pRb inactivation. Unexpectedly, NG2-Cre:pRb flox/flox mice developed pituitary tumors with high penetrance. Adenohypophysial neoplasms developed initially as multifocal lesions; by 1 year, large tumors showed brain invasion. Immunohistochemistry identified these as Pit1-lineage neoplasms, with variable immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…To the best of our knowledge there are no previous studies investigating NG2 or SOX2 expression levels in CPTs but they have been previously associated with cancer development (15)(16)(17)(18)(19)(20)(21)(22). Increased expression of NG2 has been demonstrated in a variety of head and neck cancers, glioma and pituitary cells (15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge there are no previous studies investigating NG2 or SOX2 expression levels in CPTs but they have been previously associated with cancer development (15)(16)(17)(18)(19)(20)(21)(22). Increased expression of NG2 has been demonstrated in a variety of head and neck cancers, glioma and pituitary cells (15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of NG2 has been demonstrated in a variety of head and neck cancers, glioma and pituitary cells (15)(16)(17)(18). SOX2 overexpression or gene amplification has been associated with the development of lung, esophageal, breast and gastric cancers (19-22).…”
Section: Discussionmentioning
confidence: 99%
“…In pathological situations, this marker is exhibited by all tumour types of the adenohypophysis except for the ACTH type [19]. It has also been demonstrated that NG2 modulates the prolactin type and the GH type adenomas through enhancement of cell adhesion but without influencing proliferation [19]. Previous data available in literature regarding pituitary pathology shows that a molecular mapping of the normal hypophysis, and of the various tumour types that emerge from it, serves as a useful tool for differential diagnosis and for the diagnosis of ectopic hormone-producing tissue and of metastases [20].…”
Section: Introductionmentioning
confidence: 99%
“…Besides protein S100 and GFAP, the neuroglial antigen 2 (NG2) is another controversial marker in tumours of the pituitary gland. Normally, NG2 is expressed by oligodendrocytes progenitors, pericytes, and tumour cells [19]. In pathological situations, this marker is exhibited by all tumour types of the adenohypophysis except for the ACTH type [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation